The Use of Articulate Storyline 3-Based Learning Media on the Understanding of Mathematical Concepts is Reviewed from the Learning Style - Rahmy Zulmaulida; Setiawan Setiawan; Nuratul Ikramah; Edy Saputra (Journal La Edusci, 2026)
This study aims to examine the effectiveness of Articulate Storyline 3-based learning media on students’ understanding of mathematical concepts when reviewed from learning styles. The research employed a quantitative approach using a pre-experimental design with a one-group pretest–posttest model. The participants consisted of 26 seventh-grade students of MTsN 1 North Aceh in the 2023/2024 academic year. Data were collected through a mathematical concept understanding test and a learning style questionnaire to classify students into visual, auditory, and kinesthetic categories. The collected data were analyzed using a normality test, paired sample t-test, and one-way ANOVA with the assistance of IBM SPSS Statistics version 29.00. The results showed a significant improvement in students’ understanding of mathematical concepts after the implementation of Articulate Storyline 3-based learning media. The paired sample t-test indicated a significant difference between pretest and posttest scores, demonstrating the effectiveness of the interactive learning media. Furthermore, the ANOVA results revealed no significant differences in students’ conceptual understanding based on learning styles, indicating that the media effectively accommodates diverse learning preferences. These findings suggest that Articulate Storyline 3-based learning media can enhance conceptual understanding in mathematics and provide an inclusive learning experience for students with different learning styles.